Предмет: Алгебра, автор: wehtaw

Нужна помощь, срочно!
Преобразуйте выражение:

Приложения:

Ответы

Автор ответа: Universalka
1

\displaystyle\bf\\\Big(\frac{2}{3} \cdot a^{-4} b^{-2} \Big)^{-2} =\Big(\frac{2}{3} \Big)^{-2}\cdot\Big(a^{-4} \Big)^{-2} \cdot\Big(b^{-2} \Big)^{-2} =\\\\\\=\Big(\frac{3}{2}\Big)^{2} \cdot a^{-4\cdot(-2)} \cdot b^{-2\cdot(-2)}  =\frac{9}{4} a^{8} b^{4} =2,25a^{8} b^{4}


wehtaw: Огромное Вам спасибо!!
Похожие вопросы
Предмет: Алгебра, автор: danilfondurasnikov
Предмет: Алгебра, автор: miny17